Increasing the ability to think critically through learning models Probing prompting Helpful Board Game in class VII-10 of SMP Negeri 10 Palembang - Pendo, Elisa Ramona; Waluyati, Sri Artati; Saputra, Ardiansyah (Jurnal Ilmiah Profesi Pendidikan, 2024)
The low critical thinking skills of students that researchers found when carrying out observations at SMP Negeri 10 Palembang had an impact on the learning process of students becoming passive and had an impact on the grades produced by students as seen from the lack of answers when asked questions and then the learning outcomes that still did not meet the criteria for completeness. teach. This research uses the PTK (Classroom Action Research) method which is applied to class VII-10 of SMP Negeri 10 Palembang with a total of 36 students. The implementation of this research includes 3 cycles which include planning, acting, and observing, implementation and observation. The instruments used in this research were observation sheets and pretest posttest carried out in each cycle. Based on the results obtained in this research, it was found that there was an increase in students' critical thinking abilities by using the learning model probing prompting which is proven through improvements in each learning cycle carried out, this can be seen in cycle I which reached 44% increased to 68% in cycle II then experienced an increase again in cycle III which reached 83%. Then an increase in results was found pretest-posttest What has been done has proven to be an increase pretest cycle I which reached 5.5% which increased in cycle II with an achievement of 69% and 83% in cycle III, besides that on posttest experienced an increase reaching 16% in cycle I which increased to 86% in cycle II and experienced an increase again in cycle III which reached 94%.